The Challenges of Implementing Evidence Based Practice: Ethical Considerations in Practice, Education, Policy, and Research - Amanda Farley (Social Work and Society)
Over the past century, the field of social work has evolved from grass-roots community-based movements to an intricate network of formally trained professionals promoting social research, education and practice (Klein and Bloom 1994). While social work professionals vary widely in their roles, skills, and attitudes toward the nature and future of the profession, they are united through the shared embrace of underlying ethical principles-beneficence, non-maleficence, autonomy, and justice (Freeman 2006; NASW 2008)-that guide their interactions with clients. Social workers hold in highest regard the intention to provide ethical and competent services to their clients. Nevertheless, the questions remain: How do social workers know the services they offer are ethical and competent? How do they know that they are providing the best available treatment or intervention, or that services are offered in a way that benefits clients? Is evidence-based practice (EBP) the answer to these questions?